A Acústica das capelas subterrâneas da nova igreja da Santíssima Trindade, Fátima - António P. O. Carvalho (2010)
This paper presents the interior acoustic characterization of the underground chapels of the new church of the Santíssima Trindade (Holy Trinity) in Fatima, Portugal. The results of the in situ measurements are presented regarding Reverberation Time, RASTI (with and without the use of electroacoustic reinforcement system), sound level of the HVAC equipment and airborne sound insulation indexes between chapels. The results are compared with Portuguese Catholic churches of similar volume and the subjective opinion of users of these chapels is analyzed.